2009
DOI: 10.1021/cm900047p
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Pattern Formation in the Diffusion-Controlled Reduction of HAuCl4 in Poly(vinyl alcohol) Hydrogels

Abstract: Gold nanoparticles (AuNPs) were incorporated in poly(vinyl alcohol) (PVOH) hydrogel cylinders via diffusion-controlled reductions of tetrachloroauric acid dissolved in the gels using sodium borohydride or ascorbic acid. At certain reagent concentrations, the two reducing agents formed very different hierarchical structured patterns due to their different chemical nature. Sodium borohydride reduction, which likely follows the classical "supersaturation" mechanism, results in the formation of spherical and monod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…This is due to fact that an increase in precursor ions concentration and fast reduction results in more extensive nucleation as well as depositional growth to form larger particles. Similar to this, the size of Au nps prepared in the gel was found to increase as gold precursor concentration increased [33].…”
Section: Intencity Intensitysupporting
confidence: 77%
“…This is due to fact that an increase in precursor ions concentration and fast reduction results in more extensive nucleation as well as depositional growth to form larger particles. Similar to this, the size of Au nps prepared in the gel was found to increase as gold precursor concentration increased [33].…”
Section: Intencity Intensitysupporting
confidence: 77%
“…Stability of small gold nanoparticles in general is an important requirement for further processing and utilization of such nanomaterials. In this regard, hydrogels were recently proposed as an attractive matrix for the stabilization of gold nanoparticles . However, the procedure for the preparation of well‐dispersed and size‐controlled metal nanoparticles inside hydrogel hybrid materials is still a challenge, and the physicochemical properties of such systems require more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…DNA is well known for its high affinity for noble and transition metals due to efficient coordination of purine and pyrimidine bases with metal ions, and it was recently demonstrated that this affinity can be utilized for the enrichment of transition metals in a DNA hydrogel matrix . Because the previously reported hybrid hydrogels containing metal nanoparticles were based on polymeric materials with low affinity for metal precursors, DNA hydrogels might be advantageous for providing very efficient concentrating of metal ions inside the hydrogels as well as for control nanoparticle growth. Synthetic methods for DNA crosslinking are well developed, and the interactions of DNA with gold complexes such as HAuCl 4 have already been reported .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In the last few years, NCs formed using gold NPs and PVA have been prepared in a number of ways including various photochemical, 14 heat-treating 15 and electrospinning 16 methods as well as using PVA based hydrogels instead of polymer solutions. 17,18 Sakamoto et al 14 showed that gold NPs can be prepared in PVA films in situ from Au ions and photochemically generated benzophenone ketyl radicals as reducing agent. Also, PVA alone can be used as reducing and stabilizing agent for generation of gold NPs.…”
Section: Introductionmentioning
confidence: 99%